1973
DOI: 10.1159/000245435
|View full text |Cite
|
Sign up to set email alerts
|

Ulcerative Colitis in Elderly Patients

Abstract: In a series of 303 patients with ulcerative colitis 19 developed initial symptoms after the age of 65. The clinical features of these patients are described. Six patients died in their initial attack of colitis either from acute toxic dilatation or perforation of the colon. The difficulties of diagnosis of acute ulcerative colitis in the elderly are stressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Earlier studies had reported older patients more likely to present with limited disease extent, but more severe symptoms at the time of diagnosis 2, 3. Additionally, some of their results also suggested that late-onset UC was associated with earlier surgical intervention and higher associated mortality 3, 4, 8, 9, 12. In contrast, our study found >90% of late-onset patients presented with left-sided or extensive disease and only 10.5% had symptoms categorized as severe.…”
Section: Discussionmentioning
confidence: 94%
“…Earlier studies had reported older patients more likely to present with limited disease extent, but more severe symptoms at the time of diagnosis 2, 3. Additionally, some of their results also suggested that late-onset UC was associated with earlier surgical intervention and higher associated mortality 3, 4, 8, 9, 12. In contrast, our study found >90% of late-onset patients presented with left-sided or extensive disease and only 10.5% had symptoms categorized as severe.…”
Section: Discussionmentioning
confidence: 94%
“…15 In fact, mortality rates in patients requiring urgent surgery were reported to be as high as 50%. 9,16,17 However, the number of elderly patients who underwent surgery in these reports was small. Recent reports have shown a decrease in mortality and morbidity rates.…”
Section: Commentmentioning
confidence: 95%